An updated geographic distribution of Myxobolus cerebralis (Hofer, 1903) (Bivalvulida: Myxobolidae) and the first diagnosed case of whirling disease in wild‐caught trout in the south‐eastern United States - Steven P. Ksepka; Jacob M. Rash; Brandon L. Simcox; Doug A. Besler; Haley R. Dutton; Micah B. Warren; Stephen A. Bullard (Journal of Fish Diseases, 2020)
Myxobolus cerebralis (Bivalvulida: Myxobolidae), the aetiological agent of salmonid whirling disease, was detected in 2 river basins of North Carolina during 2015, which initiated the largest spatial–temporal monitoring project for the disease ever conducted within the south‐eastern United States (focused mainly in eastern Tennessee and western North Carolina). A total of 2072 rainbow trout Oncorhynchus mykiss , 1,004 brown trout Salmo trutta and 468 brook trout Salvelinus fontinalis were screened from 113 localities within 7 river basins during June 2017 through October 2019. Infections were detected by pepsin–trypsin digest, microscopy and the species‐specific nested polymerase chain reaction (PCR) in 19 localities across 6 river basins. Myxospore morphology was indistinguishable from the published literature. In 2019, five rainbow trout that symptomatic for whirling disease (sloping neurocranium and lordosis) were captured and processed for histopathology. Myxospores were detected in the calvarial cartilage of two deformed trout with associated erosion of the cartilage consistent with reported whirling disease lesions. This is the first report of M. cerebralis in Tennessee and the first histologically confirmed cases of whirling disease in southern Appalachian (south‐eastern United States) rivers and streams and expands the distribution of M. cerebralis throughout western North Carolina and eastern Tennessee.